Exploring women's knowledge of abortion legality and association with source of abortion care using population-based survey data in Côte d'Ivoire and Ghana - Grace Sheehy; Caroline Moreau; Easmon Otupiri; Sarah Keogh; Georges Guiella; Suzanne O. Bell (BMC, 2024)
Abstract Background Knowledge of the conditions under which abortion is legal is important so that people can advocate for their right to abortion care. Yet minimal research has explored the association between women's knowledge of abortion legality and the induced abortion care they receive, particularly using population-based survey data. Methods Using national survey data collected by Performance Monitoring for Action (PMA) in Côte d'Ivoire and Ghana, we aimed to compare the prevalence of accurate knowledge of abortion legality, factors associated with knowledge of the law, and the association between knowledge of abortion legality and the source of women's induced abortion care in these two settings. We ran bivariate and multivariable logistic regressions to assess the relationships of interest. Results We found that awareness and knowledge of the abortion law were low in both Côte d'Ivoire and Ghana. In Cote d'Ivoire, women who were older, more educated, and with past abortion experience were more likely to be aware of the law. In Ghana, knowledge of the law did not vary significantly by demographic characteristics. However, in Ghana, knowledge of the law was correlated with women's use of the formal healthcare system for abortion care, with greater use of clinical sources in rural areas. Conclusions It is possible that for populations with reduced access to abortion services, such as those in rural areas, knowledge of the law is advantageous for those seeking facility-based abortion care, particularly in settings where abortion is legal for a range of indications. Interventions seeking to improve access to facility-based abortion care in settings where abortion is legal on various grounds should incorporate education on the legal grounds for abortion.